AFFECTIVE PROCESSES IN EARLY SLA: A SITUATED DEVELOPMENTAL VIEW - Mihaljević Djigunović, Jelena (2011)
One area where affective processes are considered to be of particular importance is early SLA (Nikolov 2009). Recent studies (e.g. Harris 2009, Mihaljevic Djigunovic 2011, Nagy 2009) suggest that deeper insights into the role of affective processes in early L2 learning can be obtained if they are viewed from a developmental perspective and combined with a contextualised approach. However, longitudinal studies that also take account of the multi-layered contextual aspects are still rather scarce. The talk will focus on a study carried out as part of Early Language Learning in Europe (ELLiE) - a transnational longitudinal project. The sample included close to 14, 00 young learners from seven European countries: Croatia, England, Italy, Netherlands, Poland, Spain and Sweden. They were learning English, French or Spanish as L2. Participants were drawn from metropolitan, small town and rural schools. All participants had begun L2 learning at age 6-7 years and were in their second year of L2 learning at the start of the project. Development of the following aspects of their L2 learning were observed over three years (2007-2010): attitudes, motivation and linguistic self-concept. Information was also collected on young participants' language achievements and on characteristics of the learning contexts involved. Data were gathered by means of smiley questionnaires, learner interviews, teacher interviews, parents questionnaires, classroom observation and language tests. The instruments, designed by the ELLiE research team, were administered simultaneously in all seven country contexts at specific data collection points. Findings will first be analysed from the developmental point of view. They will then be discussed in terms of their interaction with the young L2 learners' linguistic achievements and contextual factors such as out-of-school L2 exposure, socio-economic status and home support. Finally, on the basis of the presented findings conclusions will be made about the role of affective processes in early SLA.